126 A 10 year clinico-pathological study of residual/recurrent borderline ovarian tumours in young females undergoing fertility-preserving surgery. (13th November 2020) - Toomey, S; Basha Mohamed, M; Arora, R
Abstract : Introduction: Borderline ovarian tumours (BOT) have a good prognosis with a 5–8% recurrence rate. Although complete staging is the standard surgical treatment; when they occur in younger women, fertility preservation is important. Since the effect of fertility-preserving surgery on recurrence remains inconclusive, in the present study we examined the clinicopathological factors in residual/recurrent BOT. Methods: BOT diagnosed between 2010 and 2020 were retrieved using electronic records for women <40 years. Clinicopathological features of residual/recurrent BOT during this period were analysed. Results: In total, 74 BOT cases were reviewed which consisted of 42 (56.8%) serous BOT, 29 (39.2%) mucinous BOT and 3 (4.1%) seromucinous BOT. Amongst the 13 residual/recurrent BOT, all but one were serous BOT. More than half of residual/recurrent BOT had normal CA125 at presentation. The mean age was similar to the non-recurrent BOTs. Laparoscopic cystectomy was the most common initial treatment. Bilateral tumours were seen at initial surgery in 3/13 (23.1%). The time to residual/recurrent tumour ranged from 1 to 96 months. The residual/recurrent tumours were seen in the same ovary in 3/13 (23.1%), in opposite ovary in 5/13 (38.5%) and at extraovarian sites in 5/13 (38.5%). Only 2 of the 13 cases showed focal micropapillary pattern. Cytology samples were examined in 7 cases and 5 of these reported presence of epithelial cells. Majority of residual/recurrent BOT were stage 1 at initial diagnosis. All but 2 patients are currently disease free. Conclusions: Our study highlights clinicopathological factors associated with residual/recurrent BOT in young females undergoing fertility-preserving surgery.